Hubungan Antara Kesadaran Merek, Kualitas Persepsian, Kepercayaan Merek dan Minat Beli Produk Hijau - Sari, Niken Permata; Widowati, Retno (Universitas Muhammadiyah Yogyakarta, 2014)
To enrich research related to green product purchase intention this study is focused on young educated consumers in Indonesia. This is reinforced by the recent rise in green business management at several companies, but still less education and public awareness on environmental issues and healthy living. This study investigates the relationship among brand awareness, perceived quality, brand trust and purchase intention toward green product “Ades” mineral water used purposive sampling with educated young consumers as subjects. The survey with questionnaires was conducted to collect the data. By implemented structural equation modeling (SEM) the results indicate that brand awareness has a significant effect toward purchase intention. Brand awareness and perceived quality have a significant and positive effects toward brand trust. Another result in this study shows that there is no positive effect of perceived quality and brand trust toward purchase intention.